Association of impaired renal function and poor prognosis in oropharyngeal squamous cell carcinoma. Issue 10 (4th April 2016) - Homma, Akihiro; Hayashi, Ryuichi; Kawabata, Kazuyoshi; Fujii, Takashi; Iwae, Shigemichi; Hasegawa, Yasuhisa; Nibu, Kenichi; Kato, Takakuni; Shiga, Kiyoto; Matsuura, Kazuto; Monden, Nobuya; Fujii, Masato
Abstract: Background: Renal function influences decisions regarding treatment for patients with oropharyngeal squamous cell carcinoma (SCC). However, the importance of renal function in oropharyngeal SCC has not yet been reported. Methods: Four hundred sixty patients with oropharyngeal SCC treated with curative intent between April 2005 and March 2007 in 12 institutions in Japan were analyzed retrospectively. Results: Four hundred three patients (87.6%) showed a creatinine clearance (CrCl) ≥50 mL/min and 57 (12.4%) with a CrCl <50 mL/min. Age was associated with worse overall survival (OS), whereas stage IVB, radiotherapy (RT), and CrCl <50 were associated with worse OS on univariate analyses. Surgery and hypertension were associated with better OS on univariate analyses. On multivariate analysis, age, stage, hypertension, and CrCl were also found to be significantly associated with OS. Conclusion: Based on this retrospective study, impaired renal function is an independent predictor of increased risk of death in patients with oropharyngeal SCC. © 2016 Wiley Periodicals, Inc. Head Neck 38: First–1500, 2016